VPS53 mutations cause progressive cerebello-cerebral atrophy type 2 (PCCA2). Issue 5 (27th February 2014) - Feinstein, Miora; Flusser, Hagit; Lerman-Sagie, Tally; Ben-Zeev, Bruria; Lev, Dorit; Agamy, Orly; Cohen, Idan; Kadir, Rotem; Sivan, Sara; Leshinsky-Silver, Esther; Markus, Barak; Birk, Ohad S
Abstract : Background: Progressive cerebello-cerebral atrophy (PCCA) leading to profound mental retardation, progressive microcephaly, spasticity and early onset epilepsy, was diagnosed in four non-consanguineous apparently unrelated families of Jewish Moroccan ancestry. Common founder mutation(s) were assumed. Methods: Genome-wide linkage analysis and whole exome sequencing were done, followed by realtime PCR and immunofluorescent microscopy. Results: Genome-wide linkage analysis mapped the disease-associated gene to 0.5 Mb on chromosome 17p13.3. Whole exome sequencing identified only two mutations within this locus, which were common to the affected individuals: compound heterozygous mutations in VPS53, segregating as expected for autosomal recessive heredity within all four families, and common in Moroccan Jews (∼1:37 carrier rate). The Golgi-associated retrograde protein (GARP) complex is involved in the retrograde pathway recycling endocytic vesicles to Golgi; c.2084A>G and c.1556+5G>A VPS53 founder mutations are predicted to affect the C-terminal domain of VPS53, known to be critical to its role as part of this complex. Immunofluorescent microscopy demonstrated swollen and abnormally numerous CD63 positive vesicular bodies, likely intermediate recycling/late endosomes, in fibroblasts of affected individuals. Conclusions: Autosomal recessive PCCA type 2 is caused by VPS53 mutations.